Episiotomy characteristics and risks for obstetric anal sphincter injuries: a case-control study - Stedenfeldt, Mona; Pirhonen, Jouko; Blix, Ellen; Wilsgaard, Tom; Vonen, Barthold; Øian, Pål (BJOG: An International Journal of Obstetrics & Gynaecology, 2012)
Objectives To investigate the association between the geometrical properties of episiotomy and obstetric anal sphincter injuries (OASIS) because episiotomies angled at 40–60° are associated with fewer OASIS than episiotomies with more acute angles. Design Case–control study. Setting University Hospital of North Norway, Tromsø and Nordland Hospital, Bodø, Norway. Sample Seventy-four women who had one vaginal birth and episiotomy. Cases (n = 37) have sustained OASIS at birth, while controls (n = 37) had not. The groups were matched for instrumental delivery. Methods Two groups of women with history of only one vaginal birth were compared. Episiotomy scar was identified and photographed and relevant measures were taken. Data were analysed using conditional logistic analysis. Main outcome measures Mean episiotomy angle, length, depth, incision point. Results The risk of sustaining OASIS decreased by 70% (odds ratio [OR] 0.30; 95% CI 0.14–0.66) for each 5.5-mm increase in episiotomy depth, decreased by 56% (OR 0.44; 95% CI 0.23–0.86) for each 4.5-mm increase in the distance from the midline to the incision point of the episiotomy, and decreased by 75% (OR 0.25; 95% CI 0.10–0.61) for each 5.5-mm increase in episiotomy length. Lastly, there was no difference in mean angle between groups but there was a “U-shaped” association between angle and OASIS (OR 2.09; 95% CI 1.02–4.28) with an increased risk (OR 9.00; 95% CI 1.1–71.0) of OASIS when the angle was either smaller than 15°or >60°. Conclusion The present study showed that scarred episiotomies with depth > 16 mm, length > 17 mm, incision point > 9 mm lateral of midpoint and angle range 30–60° are significantly associated with less risk of OASIS. Shrinkage of tissue must be considered.